Governing markets as knowledge commons - Dekker, Erwin 1984-; Kuchař, Pavel (Cambridge University Press, 2022)
Knowledge commons facilitate voluntary private interactions in markets and societies. These shared pools of knowledge consist of intellectual and legal infrastructures that both enable and constrain private initiatives. This volume brings together theoretical and empirical approaches that develop and apply the Governing Knowledge Commons framework to the evolution of various kinds of shared knowledge structures that underpin exchanges of goods, services, and ideas. Chapters offer vivid and illuminating case studies that illustrate this conceptual framework. How did pooling scientific knowledge enable the Industrial Revolution? How do social networks underpin the credit system enabling the Agra footwear market? How did the market category Scotch whisky emerge and who has access to it? What is the potential of blockchain-ledgers as shared knowledge repositories? This volume demonstrates the importance of shared knowledge in modern society
Title from publisher's bibliographic system (viewed on 09 Dec 2021)
Introduction : governing markets as knowledge commons / Erwin Dekker and Pavel Kuchař -- The contribution good as the foundation of the industrial revolution / Terence Kealey and Martin Ricketts -- On the social evolution of knowledge / Renée Prendergast -- Individual sovereignty and coproduction of knowledge governance / Edward J. López -- Common sense commons : the case of commonsensical social norms / Brett Frischmann -- Conventions as shared cognitive infrastructures / Young Back Choi -- Property rights, knowledge commonse and blockchain governance / Darcy W.E. Allen, Chris Berg, Sinclair Davidson, and Jason Potts -- Knowledge commons, social Infrastructures and informal markets : the case of informal trade credit in India / Yugank Goyal -- Entrepreneurship and governance in scotch whisky knowledge commons / Michelle Albert Vachris and Kyle Vachris -- Trolling in the deep : managing transgressive content on online platforms as a commons / Julien Gradoz and Raphaël Raux -- Crowdfunding the queer museum : a polycentric identity quarrel / Carolina Dalla Chiesa -- Understanding different qualities of the knowledge commons in contemporary cities / Youn Sun Won and Arjo Klamer
Keywords: Knowledge economy; Intellectual property; Intellectual capital; Information commons; Theorie; Öffentliches Gut; Markt; Wissen; Aufsatzsammlung